2018
DOI: 10.1128/jvi.02221-17
|View full text |Cite
|
Sign up to set email alerts
|

Relative Abundance of Integrant-Derived Viral RNAs in Infected Tissues Harvested from Chronic Hepatitis B Virus Carriers

Abstract: Five matching sets of nonmalignant liver tissues and hepatocellular carcinoma (HCC) samples from individuals chronically infected with hepatitis B virus (HBV) were examined. The HBV genomic sequences were determined by using overlapping PCR amplicons covering the entire viral genome. Four pairs of tissues were infected with HBV genotype C, while one pair was infected with HBV genotype B. HBV replication markers were found in all tissues. In the majority of HCC samples, the levels of pregenomic/precore RNA (pgR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 88 publications
(202 reference statements)
4
38
0
Order By: Relevance
“…HBsAg can be transcribed from ccc/DNA but in HBeAg negative patients the probable predominant source of HBsAg is from RNAs transcribed from integrant HBV DNA . This source of HBsAg is relatively inaccessible without cell loss.…”
Section: Virology Of Hepatitis B and Prospects For A Curementioning
confidence: 99%
“…HBsAg can be transcribed from ccc/DNA but in HBeAg negative patients the probable predominant source of HBsAg is from RNAs transcribed from integrant HBV DNA . This source of HBsAg is relatively inaccessible without cell loss.…”
Section: Virology Of Hepatitis B and Prospects For A Curementioning
confidence: 99%
“…Integrated HBV DNA lacks the ability to transcribe pgRNA but produces novel viral‐host fusion RNA, which may have pathological functions. The relative abundance of integrant‐derived HBV RNAs (id‐RNAs) in chronically infected tissues suggest that id‐RNAs coding for the envelope proteins may facilitate the production of a considerable fraction of HBsAg in infected cells bearing HBV integrants . In patients treated with NA, HBsAg may still be high despite low transcriptional activity of cccDNA because integrated HBV DNA can maintain HBsAg production .…”
Section: Roles Of Pgrna In Disease Pathogenesismentioning
confidence: 99%
“…Since integrated HBV DNA cannot serve as the source of the progeny virus, it has been commonly assumed that the HBV life cycle is independent of HBV DNA integrants. Using liver and matching hepatocellular carcinoma (HCC) tissues harvested from individuals that were chronically infected with HBV and that were not treated with anti-HBV drugs, our recent study demonstrated that RNA transcripts arising from integrated HBV DNA (i.e., HBV integrant-derived RNAs or id-RNAs) were abundantly or even predominantly present, when compared to viral RNAs transcribed from the episomal, covalentlyclosed circular viral DNA (cccDNA) (i.e., replication-derived or rd-RNAs) [4]. The observed relative abundance of id-RNAs suggested that these RNA molecules could serve as a considerable source of the HBV envelope proteins (or surface antigen, HBsAg) that is independent of the HBV genome replication.…”
Section: Commentarymentioning
confidence: 99%
“…The data further suggested that id-RNAs/id-HBsAg therefore can possibly influence the maintenance of the chronic state of HBV infection. In addition, the study proposed to revise the current model of the HBV life cycle by incorporating the potential contributions of id-RNAs and id-HBsAg as described above [4]. Moreover, it became apparent that the inability of current anti-HBV drugs to achieve loss of serum HBsAg in the vast majority of treated patients can be likely explained by significant amounts of id-HBsAg that are translated from id-RNAs independently of HBV replication [4].…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation